Study on water quality at Tasik Chini, Pahang - Jia Xin, Jong (2013)
The purpose of the study were to determine the characteristic of water quality at Tasik Chini (Chini Lake) and to obtain the water quality classification based on WQI (Water Quality Index) of the selected sampling stations. A total of five sampling stations were selected for this study: Laut Gumum, Laut Jerangking, Laut Kenawar, Laut Melai and Laut Pulau Balai. Eleven water quality parameters were analyzed based on in- situ and ex-situ analysis during dry and rainy day. Laboratory analysis carried out according to the HACH method. In-situ water quality were including pH, dissolved oxygen, conductivity, turbidity and temperature. For ex-situ water quality parameters included TSS, ammoniacal nitrogen, COD, BOD, total coliform and E-coli. The result show that based on Malaysia WQI, the water in Tasik Chini is classified as Class II which suitable for recreational activities and body contact. However, recent activities such as illegal logging, iron mining, agricultural and industrial activities have taken place in surrounding of the lake consequently affected the water body of Tasik Chini thus undergone devastating changes.